2003
DOI: 10.1002/ajmg.c.10013
|View full text |Cite
|
Sign up to set email alerts
|

Mental deficiency, alterations in performance, and CNS abnormalities in Overgrowth syndromes

Abstract: Mental deficiency, alterations in performance, and central nervous system (CNS) abnormalities are discussed in the following overgrowth syndromes: Sotos syndrome, Weaver syndrome, Proteus syndrome, neurofibromatosis type 1, fragile X syndrome, syndromes with neonatal hypoglycemia, Simpson-Golabi-Behmel syndrome, hemihyperplasia, Sturge-Weber syndrome, Bannayan-Riley-Ruvalcaba/Cowden syndrome, macrocephaly-autism syndrome, PEHO syndrome, chromosomal syndromes, and other miscellaneous syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 99 publications
0
35
0
4
Order By: Relevance
“…The signs of macrocephaly and facial features are considered to be essential in the diagnosis of Sotos syndrome [10,11,12]. Furthermore, there is an increase in bone age to more than the 90th percentile, affective and behavior abnormalities accompanied by mental retardation, and general motor and developmental dysfunction due to hypotonia have been reported [1,13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signs of macrocephaly and facial features are considered to be essential in the diagnosis of Sotos syndrome [10,11,12]. Furthermore, there is an increase in bone age to more than the 90th percentile, affective and behavior abnormalities accompanied by mental retardation, and general motor and developmental dysfunction due to hypotonia have been reported [1,13,14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…However, such abnormalities and retarded functions which occur in children of less than 5 years of age show a tendency of improvement with increasing age according to several studies [1, 2, 13, 15]. It has also been observed that the incidence of cardiac abnormalities, such as arterial septal defect, ventricular septal defect and patent ductus arteriosus increase 10-fold in patients with Sotos syndrome [16], and since there is an increased risk for malignant tumors in Sotos syndrome, regular clinical examination of such patients has been emphasized [17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Cole and Hughes 6) described the clinical characteristics of this syndrome, and it consists of macrocrania, general overgrowth, long cranium, narrow face, and mental retardation, and accompanying neuroradiologic manifestations are hydrocephalus, subdural fluid collection, midline abnormalities such as the cavum septum pellucidum, kyphoscoliosis, and cardiac defects 4,7,8,16) . Developmental delay and seizures, and attention deficit may also present 5,6,15) . Clinical criteria include facial gestalt, macrocephaly, advanced growth, and the presence of developmental delay 6,19) .…”
Section: Introductionmentioning
confidence: 99%
“…Atraso para andar até depois de 15 meses e atraso na fala até depois dos 30 meses é comum nesta síndrome (Höglund et al, 2003;Cohen, 2003).…”
Section: I21 -Aspectos Clínicosunclassified
“…Sialorréia é também constantemente observada e o "déficit" de atenção pode ocorrer em alguns casos (Cohen, 2003). Já foi relatado também, em pacientes com a síndrome de Sotos, anormalidades como ausência de corpo caloso, sulco cortical proeminente, cavum septum pellucidum e cavum velum interpositi.…”
Section: I21 -Aspectos Clínicosunclassified